Diversification of Economy - An Insight into Inclusive Growth & Food Security with Special Reference to Pakistan’s Agriculture Economy - Dixit, Pankaj; Ahmed, Ramyar Rzgar; Yadav , Arvind Kumar; Lal, R.C (Asian Journal of Agriculture and Rural Development, 2019)
In order to improve agricultural economies, diversification is an important step to deal with the challenges of both the present and the future. This research attempted to deal with the above challenges of different economies as well as Pakistan’s economy to achieve inclusive growth through internal diversification and reforms. The main objective of this paper is to see how internal diversification and land reform can prove to be a milestone in tackling the above challenges. In order to perform numerical and qualitative analysis of primary and secondary data, the descriptive statistics is being used. As a result, it was shown that through internal diversification and land reforms, Pakistan's agricultural economy can be strengthened. At the end of the paper, some effective suggestions have been proposed, which will be important in achieving the aforementioned objectives.